Cell Membranes as Therapeutic Targets: Implications in Infectious and Metabolic Disorders - Hetvi H. Patel; Hardini P. Chauhan; Maitry H. Rathod; Vaibhavi J. Panchal; Bisojeet R. Khandai (International Journal of Membranes, 2026)
This is a review of the crucial role played by cell membranes in health and disease with respect to their contribution to infectious and metabolic diseases. Dysfunction of membranes, such as membrane transporter changes and changes in lipid content, has been associated with a variety of diseases, including diabetes, cardiovascular disease, and cancer. The present therapeutic approaches are focused on attacking membrane constituents by disrupting the entry of pathogens or dysfunctional membrane proteins, which have potential as therapies for infections, metabolic disorders, and cancer. Examples are SGLT2 inhibitors to treat diabetes and CCR5 inhibitors to treat HIV. Moreover, nanotechnology, gene editing, and individualized treatment are giving new prospects for more specific and efficient treatment. The applications of membrane-targeted therapies are enormous, and future studies are bound to allow therapeutic agents to be delivered more effectively and produce better treatment results. This paper brings to light the present methods as well as the future perspectives of the membrane-targeted therapies and provides an insight into the potential of the same in the treatment of complex diseases.
Keywords: Ccr5-inhibitors; Gene Editing; Metabolic disorders; Personalized medicine; SGLT2-inhibitors; cell membranes; membrane dysfunction; membrane transporters; nanotechnology; therapeutic strategies